Students' Ability In Writing Descriptive Text At TheEight Grade Of SMP N 3 Sawit In 2013/2014 Academic Year - Yanti, Astri, Drs. Djoko Srijono, M.Hum, Dr.Dwi Haryanti, M.Hum (2014)
The aims of this study is to know the students' ability in writing descriptive text, the content and organization of descriptive text, the students vocabulary, grammar, and mechanism in writing descriptive text at the eight grade of SMP N 3 Sawit in 2013/2014 academic year. This research is a descriptive research. The methods of collecting data are writing test and analyzing document. Data of this research are the students' writing of descriptive text. The data source of this research are the informant and writing test. The technique for analyzing data is (1) Reading the students' work sheet in the form of descriptive text. (2) Analyzing the aspects of descriptive text; content, organization, vocabulary, grammar and mechanic. (3) Classifying and scoring the students test of writing descriptive text. (4) Drawing conclusion based on the result of the research of the students' ability in writing descriptive text. Based on the research finding, the writer concludes that the students' ability in writing descriptive text at the eight grade of SMP N 3 Sawit in 2013/2014 accademic year is fair. 7 students belong to good category (the score 70-84) or 23,33%. There are 23 students belong to fair category (the score 55- 69) or 76,67%, and there is no student who belongs to very good and poor category. The aspects in writing descriptive text can be seen that the content belongs to good category with the best average is 72,33. Mechanism belongs to fair category, and the smallest average is 60,5. Grammar belongs to fair category with the average is 64,16. Organization belongs to fair category with the average is 66,83. Vocabulary belongs to fair category with the average is 67,5. It means that the aspect in writing descriptive text mastered by the students at the eight grade of SMP N 3 Sawit is fair.